2015
DOI: 10.1167/iovs.15-17595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Rho Kinase Inhibitor Y-27632 on Corneal Endothelial Wound Healing

Abstract: ROCK inhibitor may be developed as an eye drop for treating acute corneal endothelial damage to prevent progression of bullous keratopathy. (University Hospital Medical Information Network Clinical Trial Registry no. UMIN000003625; www.umin.ac.jp/ctr).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 40 publications
2
65
2
2
Order By: Relevance
“…These positive changes were maintained up to the final examination, two years later in this case [35]. Last, but not least, in 2015, Okumara et al [31] reported on 3 patients who had severe corneal endothelial damage due to cataract surgery and received Y27632 eye drops. Two of them received 1 mM Y27632 eye drops administered 6 times daily in the first 4 months, and 4 times daily during the following 2 months; the third patient used the drug four times daily only for 3 months.…”
Section: Corneal Wound Healingmentioning
confidence: 58%
See 3 more Smart Citations
“…These positive changes were maintained up to the final examination, two years later in this case [35]. Last, but not least, in 2015, Okumara et al [31] reported on 3 patients who had severe corneal endothelial damage due to cataract surgery and received Y27632 eye drops. Two of them received 1 mM Y27632 eye drops administered 6 times daily in the first 4 months, and 4 times daily during the following 2 months; the third patient used the drug four times daily only for 3 months.…”
Section: Corneal Wound Healingmentioning
confidence: 58%
“…The third patient had an intact Descemet membrane but the corneal endothelial cell density was critically low (508 cells/mm 2 ). Contrary to expectations, by the third month, the cornea became clear and the visual acuity increased from the initial 20/63 to 20/25 [31]. Although these human studies have a number of limitations, for example patients without treatment were not followed and the results are very preliminary, taken together they suggest that ROCK inhibitors may be effective in reducing corneal edema, and/or improve wound healing.…”
Section: Corneal Wound Healingmentioning
confidence: 79%
See 2 more Smart Citations
“…In a recent clinical study, Okumura et al noticed that the use of a topical ROCK inhibitor (Y-27632) could recover corneal transparency in patients with severe corneal oedema following cataract surgery. The authors concluded that ROCK inhibition promotes proliferation of the residual undamaged endothelial cells 19. In addition, previous studies have demonstrated that severe damage to CECs leads to their fibroblastic transformation and a loss of the endothelial cell pump and its barrier function.…”
Section: Introductionmentioning
confidence: 96%